1990
DOI: 10.1037/0022-006x.58.6.768
|View full text |Cite
|
Sign up to set email alerts
|

Patient and therapist introject, interpersonal process, and differential psychotherapy outcome.

Abstract: The Structural Analysis of Social Behavior (SASB; Benjamin, 1974Benjamin, ,1982Benjamin, ,1984 system was used to study the interpersonal process between patient and therapist in the 3rd session of 14 therapeutic dyads. Dyads were grouped into good and poor outcomes cases (n = 7) on the basis of the amount of change in the patients' introject as measured by the INTREX Introject Questionnaire (Benjamin, 1983). Strong support was found for the following hypotheses based on interpersonal theory, linking therapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
307
7
17

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 336 publications
(357 citation statements)
references
References 23 publications
(18 reference statements)
24
307
7
17
Order By: Relevance
“…We were especially interested, from a theoretical standpoint, in the possible role of therapists' intrapsychic structure. Prior research has shown that therapists with certain self-hostile introjects engage in greater frequencies of countertherapeutic interpersonal process, such as complex communication (Henry, Schacht, & Strupp, 1990). In our earlier article (Henry, Strupp, Butler, Schacht, & Binder, 1993), we reported a significant increase in complex communications at the group level after training.…”
Section: Tural Analysis Of Social Behavior (Sasb) and The Vanderbilt mentioning
confidence: 79%
“…We were especially interested, from a theoretical standpoint, in the possible role of therapists' intrapsychic structure. Prior research has shown that therapists with certain self-hostile introjects engage in greater frequencies of countertherapeutic interpersonal process, such as complex communication (Henry, Schacht, & Strupp, 1990). In our earlier article (Henry, Strupp, Butler, Schacht, & Binder, 1993), we reported a significant increase in complex communications at the group level after training.…”
Section: Tural Analysis Of Social Behavior (Sasb) and The Vanderbilt mentioning
confidence: 79%
“…Patients and therapists were asked how they treat themselves at their best or worst in various interpersonal interactions; the answers provide measures of affiliative and autonomous introject styles (Pincus, Newes, Dickinson, & Ruiz, 1998). In this study, we used only ratings of "yourself at your worst", which is consistent with previous research (Henry, Schacht, & Strupp, 1990). The RSQ consists of 32 items that assess adult attachment styles, and include secure, preoccupied, fearful, and dismissing styles.…”
Section: Personality Assessmentmentioning
confidence: 87%
“…Henry, Schacht, and Strupp (1986), for example, used a strategy based on Benjamin's (1974) Structural Analysis of Social Behavior (SASB) to compare 4 therapists, each of whom saw a good outcome and a poor outcome case. The first 15-20 minutes of the third session in each of the eight cases was coded on the SASB because "prior research had indicated that the nature of the working alliance in time-limited therapy is well-established by this time and that this alliance predicts eventual therapeutic outcome" (Henry et al, 1986, p. 28).…”
Section: The Case Comparison Methodsmentioning
confidence: 99%